#Drugsforsale: An exploration of the use of social media and encrypted messaging apps to supply and access drugs - Moyle, L.; Childs, A.; Coomber, R.; Barratt, Monica (Elsevier BV, 2019)
© 2018 Background: The use of new technology is frequently harnessed by drug suppliers to both increase profits and reduce risk. While a growing body of research has investigated drug sales through online pharmacies and cryptomarkets, despite growing media interest, no published research exists on how smartphone-enabled social media and messaging applications (‘apps’) are utilised in the drug economy. This study analyses the ways such apps (e.g. Snapchat, Instagram and WhatsApp) are utilised to supply and access drugs. Methods: Three data collection methods were employed: an international online survey of 358 drug users that had either used or considered using apps to access drugs; ‘rapid’ interviews (n = 20) with a similar population; and in-depth interviews (n = 27). Key issues explored were the perceived benefits and risks associated with sourcing drugs through apps, with specific attention paid to novel supply and purchasing practices. Results: Apps appear to provide a quick, convenient method for connecting buyer and seller. They were often viewed as a valuable intermediary option between cryptomarkets and street dealing, providing ‘secure’ features and the opportunity to preview product without the requirement for technical expertise. Apps are used in a range of novel and diverse ways, including as social networking spaces in which drugs are advertised, and as encrypted messaging services for communicating with known sellers and arranging transactions. Key anxieties related to potential for exposure to law enforcement and legitimacy of substances. Conclusion: Though ‘social supply’ through friends is still typically preferred and there is a degree of wariness toward app-mediated supply, our data indicate that apps are fast becoming a viable option for accessing drugs. Apps can provide an easily accessible platform that connects buyers with commercial drug suppliers and substances that may otherwise remain elusive. Potential harms can be reduced through the provision of information which demystify common-sense assumptions that apps are secure and that this ‘visual’ drug economy promotes safer purchasing practices.